Implementasi Program Makan Bergizi Gratis (MBG): Studi Kasus di RA X Kabupaten Jember - Irfiah Irfiah; Izatul Milla (Universitas Islam Jember, 2026)
This study aims to analyze the implementation of the Free Nutritious Meal Program (MBG) at RA X in Jember Regency based on the aspects of communication, resources, implementer disposition, and bureaucratic structure. This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observation, and documentation involving parents as the main informants. Data analysis was conducted using an interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the communication aspect has not been optimal due to limited socialization and lack of information transparency. The resource aspect is considered adequate but does not fully align with the children’s preferences. The implementers’ disposition reflects a positive attitude but lacks active parental participation. Meanwhile, the bureaucratic structure operates routinely but lacks a well-structured evaluation mechanism. Overall, the program implementation has not shown a significant impact on children's eating behavior and health conditions.